Poaching: Get a grip on it - Aryal, Ravi S (Himalayan Journal of Sciences, 2006)
One of the causes of critical species depletion in the world is the increasing demand for wildlife products. Poaching, for example of rhinoceros, has long been rampant in Nepal, and has recently been facilitated by the reordered priorities and shifting constraints of the current emergency. The best hope for stopping or reducing the illegal exploitation of protected species lies in the empowerment and involvement of local people in conservation work. Better training, modern communication equipment, and reorganization of the anti-poaching units would prove beneficial in reversing a disturbing trend that threatens to undo even the limited successes of the past three decades of conservation.Himalayan Journal of Sciences 1(2): 73, 2003The full text is available at the Himalayan Journal of Sciences website